2009
DOI: 10.1016/s0301-0546(09)71108-5
|View full text |Cite
|
Sign up to set email alerts
|

Skin prick test reactivity to common aeroallergens among allergic rhinitis patients in Iran

Abstract: Our work showed the importance of weeds, especially the Amaranthaceae and Chenopodiaceae families. Diagnosis of pollen allergy can be simplified by using a combination of a few common aeroallergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
56
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 26 publications
11
56
2
Order By: Relevance
“…Many epidemiological studies have revealed a progressive increase of the allergic rhinitis during recent decades (1)(2)(3). Allergic rhinitis is characterized by nasal symptoms including sneezing, runny nose, itching and nasal congestion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many epidemiological studies have revealed a progressive increase of the allergic rhinitis during recent decades (1)(2)(3). Allergic rhinitis is characterized by nasal symptoms including sneezing, runny nose, itching and nasal congestion.…”
Section: Introductionmentioning
confidence: 99%
“…Allergic rhinitis caused by a complex interaction of genetic factors and environmental influences. One of the most important environmental factors is aeroallergens, such as pollens, fungal spores, house dust mites, etc (2,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, another study in Iran9 found that dust mite allergy is only positive in 20% of the subjects. 9 On the contrary, Saleh et al 10 found that the allergen with the most positive results is mold. 10 The difference in the dominant allergens can be attributed to the different demographic factors which can influence the types of allergen presence in there.…”
Section: Discussionmentioning
confidence: 97%
“…Several epidemiological, environmental, and clinical studies were focused on the relevant species like Alternaria, Aspergillus, Cladosporium and Penicillium (7). Airborne allergens with fungal origin have been implicated as one of causes of allergic respiratory diseases in our region and neighbor countries (8).…”
Section: Introductionmentioning
confidence: 99%